Media Theology: New Communication Technologies as religious constructs, metaphors, and experiences. (January 2017) - Blondheim, Menahem; Rosenberg, Hananel
Recent studies have seen religious observance as inherently related to available communication technologies. This study follows this thrust but complements the focus on religious praxis with a look at media theology —the ideological dimension of the religion and media nexus. It traces three distinct facets of media theology: the way religious sensibilities affect how we create, shape, apply, and establish a relationship with media technologies; how media technologies serve as tools for grasping aspects of theology; and finally, how media use can launch mental and existential religious experiences. The study's orientation is historical, charting the development of the relationship between media technologies and the religious mind in the Abrahamic religions from the biblical media of fire and cloud through script and electric communications and all the way to the Internet.